Implementasi Perubahan Sistem Informasi Keuangan pada Kantor Imigrasi Kelas I Non TPI Karawang - Atik Srirahayu; Dwi Epty Hidayaty; Ery Rosmawati (J-MAS (Jurnal Manajemen dan Sains), 2022)
Financial management in government agencies is very important as it has a "specific" concept of performance, namely responsibility, synergy, transparency and innovation. The financial information system is one of the tools used to record various information system transactions that affect the operation and management of business support activity. The financial management process in the work unit of the Class I, Non-TPI Immigration Office in Karawang can be considered less effective and efficient as it goes through multiple stages with different applications, which underlie changes in the use of financial information. This article is to explain the implementation of changes in the financial information system in the Immigration Service Class I No TPI Karawang The method of writing this article is to combine descriptive qualitative research methods with observations, use of survey techniques, analysis, interpretation of data. and triangle. The results obtained are (1) Changes in the application system in the work unit of the Immigration Office Class 1 Non TPI Karawang generally facilitate tasks and work for users. (2) Comparing time effectiveness is not very important, but using an application to be able to perform different types of financial operations can minimize the occurrence of errors or non-response on a PC during the recording work. (3) The effectiveness of the work summary occurs in the reconciliation phase, where with the latest system the E-Recon reconciliation process between the work units and the PCPN is automated (it is not necessary to use CDA (Computer Data Archive). ) of ABAS (Accrual Based Accounting System) in E-Commerce.econ). (4) The SAKTI application can replace the 6 previous applications used in the Karawang Class 1 Immigration Office. (5) Changes in the financial information system do not reduce the existing existing tasks and functions as financial documents.